PENGARUH SPESIALISASI INDUSTRI KAP, REPUTASI AUDITOR, DAN AUDIT TENURE TERHADAP AUDIT REPORT LAG - Dharma Nirmala Eka Makhabati; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2019)
The longer delay in the publication of financial statement can reduce the value of financial information because it is not available at the time required. This research aims to empirically examine the effect between auditor industry specialization, auditor reputation, audit tenure on audit report lag. The dependent variable in this research is audit report lag. The independent variables in this research are auditor industry specialization, auditor reputation, and audit tenure. While the control variables used in this research are leverage, subsidiary, family ownership, and loss. The population of research consist of 49 financial reporting from chemical companies that listed in Indonesia Stock Exchange period 2013-2017. This research using secondary data that selected by purposive sampling method, so the final sample that obtained are 41 companies. The analytical method that was used is multiple linear regression analysis, which is processed using SPSS 23. The result of this research shows that auditor industry specialization and auditor reputation have negative and significant effect to audit report lag. This means that if the company audited by auditor industry specialization or auditor the Big 4, then the audit report lag will be shorter than the company audited by auditor non industry specialization or auditor non the Big 4. While audit tenure has insignificant effect to audit report lag.